2011
DOI: 10.1177/1059840511399289
|View full text |Cite
|
Sign up to set email alerts
|

Connecting With Frequent Adolescent Visitors to the School Nurse Through the Use of Intentional Interviewing

Abstract: Nurses as accessible, helping adults within schools have daily opportunities to reach adolescents with unmet mental health needs. Understanding the relationship between frequent clinic visits or somatic complaints as a sign of underlying problems, which may be organic or psychoemotional in origin, requires the unique skill set of the school nurse. The welcoming school nurse, who cares for students with acceptance and emotional availability, nurtures the development of trust and meaningful personal connection. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Providing copies of work on this topic (Hojat, 2009;Kelley et al, 2011;Neukrug, Bayne, Dean-Nganga, & Pusateri, 2013;Pavletic, 2011) will give learners a framework on which to build a thorough understanding of the principles of effective compassionbased, empathetically enhanced communication.…”
Section: Professional Development Implicationsmentioning
confidence: 99%
“…Providing copies of work on this topic (Hojat, 2009;Kelley et al, 2011;Neukrug, Bayne, Dean-Nganga, & Pusateri, 2013;Pavletic, 2011) will give learners a framework on which to build a thorough understanding of the principles of effective compassionbased, empathetically enhanced communication.…”
Section: Professional Development Implicationsmentioning
confidence: 99%
“…The importance of the relationship between SNs and adolescents with health complaints is highlighted by Pavletic [ 22 ] and Svebak et al [ 23 ], who found that the level of student complaints tended to decline with access to the school nursing service. Further, Borup et al [ 24 ] concluded that visiting the SN might reduce students’ proneness to the use of medication when they experience aches and psychological problems.…”
Section: Introductionmentioning
confidence: 99%
“…Creating an atmosphere of trust and confidence was seen as a key to promoting health. [19,20] A caring school nurse was perceived as supportive of adolescents. [21] From the adolescents' point of view, confidentiality and trust were important factors when seeking help.…”
Section: Introductionmentioning
confidence: 99%
“…The SHS is led and managed by the principal of the school and includes professions such as school nurses, school physicians, psychologists, guidance counselors and special education teachers. [1] In upper-secondary school, the school nurse invites each student aged [16][17][18][19] to a health dialogue during the first year with the aim of promoting and strengthening the health of the student. [2] Various health and lifestyle questionnaires have been developed and used during the health dialogue.…”
Section: Introductionmentioning
confidence: 99%